Tahap penerimaan banduan terhadap hukuman mati - Abdul Aziz, Abdul Razak (2014)
Death penalty is a form of punishment which is applied in some countries of the world, whereby Malaysia is one of them. The death penalty was first introduced in Malaysia during the British colonial era. Acceptance of the death penalty among death row prisoners attributes to various factors which includes emotional factors that are either positive or negative which ranges from high, medium and low levels. A lot of studies had been conducted in western countries related to death penalty among prisoner. Studies among death row prisoners in Malaysia is very limited due to security reasons, researchers does not have easy access to death row prisoners. The research shows that death row prisoner’s involvement in serious crime attributes to their financial problems in order to obtain drugs, peers, and the surrounding environment. Apart from that, this study also looked into the causes of emotional distraught which have resulted in personal and organizational threats and endangerment. It is often the case when many inmates lose their patience due to the extended time taken to appeal or ask for clemency at the courts of appeal. Structured interviews were also utilized with the help of the Nvivo software. Data were analyzed for the purpose of obtaining an overview of research on the issues and themes based on qualitative analysis. In this research, some of the issues and themes were developed to fit with the theory and literature review such as the acceptance of death penalty prisoners engage in serious criminal and emotional factors interfere with the prisoner. The finding of this study also shows that the acceptance of death row prisoners towards death sentence is accepted as reciprocation from god. This research contributes towards the field of social work, particularly criminology, correctional and the policy management for the well-being of death row prisoners in Malaysian Prison Department.